Avaliação do potencial antioxidante de extratos encapsulados de mirtilo - Bianchi, Ana Paula (2017)
Consumers are increasingly concerned about health and well-being in general. This is due to the increase in cases of chronic and degenerative diseases, which are caused not only by an increase in life expectancy, but also by long-term changes in lifestyle, such as unbalanced diets and sedentary lifestyle. The health agencies nowadays recommend a series of care with food and health in general. Faced with this, functional foods have become a new and promising trend in the food and pharmaceutical industry. Blueberry (Vaccinium sp.) Is a fruit that is gaining prominence in this segment of the industry, caused by the recognition of its therapeutic properties. These are mainly due to the presence of phenolic compounds, which play an antioxidant activity capable of contributing to the prevention of diseases. Because it is a fruit of small production and of short useful life, it becomes necessary the application of processing technologies that maintain the desired properties. The spray-drying technique associated with encapsulation is intended to provide the protection of the substances of interest, since it avoids the direct counting of them with light and heat. This has enabled a greater supply of food with functional potential and longer shelf life, while adding commercial value to the products developed. The mastery of the processing techniques for blueberry, and the knowledge of the maintenance of the functional properties of elaborated products is of paramount importance for the industry that wishes to stand out in the branch of functional foods. This study aimed to characterize two blueberry encapsulated extracts produced in the north of Rio Grande do Sul. We tested two encapsulating agents: gum arabic (GA) and whey protein concentrate (CPS). From the encapsulated extract that presented the best functional, morphological and sensorial response, the study was continued with this extract, carrying out stability tests of the bioactive compounds during the shelf life and verifying their antioxidant behavior also in an in vivo test, using as a model The yeast Saccharomyces cerevisiae. As morphological tests of the encapsulation of the extracts we used the Encapsulation Efficiency (EE) and evaluation of the external morphology of the microcapsules by Scanning Electron Microscopy (SEM). Color analysis was performed as a sensorial attribute. To verify the functional potential we evaluated the total and individual phenolic compounds by High Performance Liquid Chromatography (HPLC) and measured the antioxidant activity by DPPH. Our results were more satisfactory with the extract encapsulated with GA (E1) with respect to morphology, color analysis and functional potential. In this way, E1 was selected to continue the study, where we obtained a reduction of phenols and total flavonoids during storage at 4º C for 5 and 10 months. In relation to the stability of the antioxidant activity against temperatures of -18, 4 and 25º C for 4 weeks, we obtained significant losses at all temperatures, but better results were obtained when the extract remained under freezing (-18ºC). In our in vivo test, the use of E1 in iron-stressed Saccharomyces cerevisiae cells was able to reduce lipid peroxidation through the TBARS method and increase GPX activity. Our study has proven that the blueberry extract encapsulated with gum arabic has maintained the antioxidant functionality present in the fruit and can be a promising ingredient in the development of functional foods. It is suggested that the industries of interest should ensure proper conservation to avoid degradation of the bioactive compounds and thus ensure longer shelf life to the product.